Teaching and Learning Music in Digital Era: Creating Keroncong Music for Gen Z Students Through Interpreting Poetry - Supiarza, Hery; Sarbeni, Irwan (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This study aims to examine the ability of ‘Z Generation’ students to interpret poetry. The z generation lives in the digital technology era where they tend to possess liberal and intelligent character. Poetry was chosen since this literature type has historical closeness to Keroncong music, especially in the Keroncong Stambul and Keroncong eras in the 1950s. The issue of Keroncong, whose development has been stagnant since the 1980s, is expected to trigger the Z generation to emerge a solution in the form of Keroncong music. The action research model used in this research was implemented through 6 stages: preparation, implementation, production, mixing and mastering, discussion and evaluation, upload, and publication. This project was applied to 33 students who were divided into five groups of 6 to 7 members each. Each group received a different poem. The project resulted in 5 Keroncong works and emerged a new Keroncong music genre called ‘Kroncongisasi Puisi.’ The study found that the learning achievements of the Z generation were achieved due to several factors: (1) their brilliant abilities in accessing various information digitally; (2) the digital age contains all the information they need; (3) their liberal nature makes them open to modernity. Regarding the process of creating Keroncong, the researcher found ten steps in the composting process: 1) interpretation, 2) composing song melody, 3) implementing the melody with accompanying musical instruments, 4) creating harmony framework, 5) practicing, 6) recording, 7) Mastering, 8) Shooting, 9) editing, 10) publishing. This study result was recommended to the Keroncong community, government, and education community.